The language of emotions : an ostensive-inferential study - Strey, Cláudia (2016)
This dissertation aims to broaden relevance theory scope in order to account for emotions in communication, evaluating its descriptive-explanatory potential. This work consists of three independent chapters, and each one of them comprehends one research question and its corresponding hypothesis. The first chapter provides the basis for the arguments developed in the subsequent chapters. It explores the study of emotion in philosophy of language and in neuroscience. The second chapter develops Sperber and Wilson’s (1986/1995, 2015) relevance theory in order to argue for a broader pragmatics, which involves both verbal and non-verbal behaviours (in line with Wharton, 2009). The focus was mainly on how natural behaviours, such as facial expressions and prosody, convey emotions. The third and last chapter reorganise relevance theory in order to explain emotional communication. It is proposed the existence of two levels of communication: a propositional one and an emotional one, both relevance-driven. I finally argue that non-verbal behaviours, words and descriptions of emotion and loose uses of language encode emotionalreading procedures that help guide the comprehension process in order to yield cognitive-affective effects. This work seeks to provide theoretical improvements to relevance theory so it can explain the language of emotion.